Pengaruh Motivasi Kerja terhadap Kinerja Dokter dalam Kelengkapan Pengisian Rekam Medis dengan di Moderasi Karakteristik Individu (Studi di Rumah Sakit Islam Unisma Malang) - Lihawa, Cicilia; Noermijati, .; Rasyid, Harun Al (Jurnal Aplikasi Manajemen, 2016)
Abstract: One of the parameters for determining the quality of health services in hospitals is the information documented in a good and complete medical record (MR). Medical record completion by a physician within 24 hours is a standard quality of care in UNISMA Islamic Hospital Malang. One of these indicators that has not yet been achieved is the 24 hours postadmission MR completion rate of 50% from the 100% standard. This study aims todetermine the impact of work motivation on physician performance in completing MR, moderated by the individual characteristics (gender, age and tenure). This study is an observational researchusing cross sectional approach, involving 45 physicians as respondents. Data were collected using questionnaires and MR completion checklists, with five medical records assigned to each respondent, and were analyzed using linear regression test. The results showedthat gender, age, and years of service do not moderate the impact of work motivation on physician performance in completing MR (p â‰¥ 0,05). This suggests that the management team does not need to consider individual characteristics in an effort to improve the physi- cian performance in completing MR through increased motivation.